Secured Autonomous Agent-Based Intrusion Detection System (SAAIDS) - Luqmanulhakim Mohd Nasir (Universiti Sains Islam Malaysia, 2024)
Thesis (M.Sc)-- Faculty of Science and Technology, Universiti Sains Islam Malaysia, 2011